Conversations about Philosophy. - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Philosophy, Volume 2, is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading researchers with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. Brian Epstein, Associate Professor of Philosophy at Tufts University;2. Onora O'Neill, Emeritus Professor of Philosophy at the University of Cambridge and a crossben.